Proceedings of the 1st International Conference on Education Social Sciences and Humanities (ICESSHum 2019) 2019
DOI: 10.2991/icesshum-19.2019.111
|View full text |Cite
|
Sign up to set email alerts
|

Association between types of domicile and nutritional status of college students in Indonesia

Abstract: Nutritional status is a requirement of a person's health convinced by the diet, the levels of nutrients containing in the body, and normal metabolic integrity. Types of domicile generally impact the behavior of daily consumptions, which further can affect the health of students. The objective of this study was to identify the types of domicile associated with the nutritional status of college students in Indonesia University of Education. Nutritional status was assessed based on body mass index, and categorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Living on academic campuses may be helpful for practicing healthy eating through access to appropriately balanced foods and beverages [85], but achieving this effect requires an implementation of policies and practices that support healthy eating and physical activity [86]. The study showed no differences in changes in food intake and in DQI after accounting for both residences before and during the study, which is consistent with the results of the study by [87]. The lack of differences may be linked to the female sample of respondents, who show more interest in a healthy diet also when living in a dormitory [83].…”
Section: Relationship Between Diet In Early Adulthood and Other Varia...supporting
confidence: 86%
“…Living on academic campuses may be helpful for practicing healthy eating through access to appropriately balanced foods and beverages [85], but achieving this effect requires an implementation of policies and practices that support healthy eating and physical activity [86]. The study showed no differences in changes in food intake and in DQI after accounting for both residences before and during the study, which is consistent with the results of the study by [87]. The lack of differences may be linked to the female sample of respondents, who show more interest in a healthy diet also when living in a dormitory [83].…”
Section: Relationship Between Diet In Early Adulthood and Other Varia...supporting
confidence: 86%
“…Indonesian students who study abroad are experiencing many changes in order to adapt to the new environment, including a change in eating habits 1 . A previous study by Doo and Kim (2017) indicated that changing dietary habits among international students might increase the risk of obesity 2 .…”
Section: Introductionmentioning
confidence: 99%